Towards development of cyber-physical systems based on integration of heterogeneous technologies. (2018) - Choi, SangSu; Kang, Gyhun
Cyber-Physical System (CPS) is a concept expanded from embedded computing and is applied to various industries such as aerospace, energy, transportation, and medical industry. Manufacturing industry is also improving its competitiveness through building CPS and is establishing environments for smart manufacturing. CPS in the manufacturing industry plays the role of controlling an entire process of product design, procurement, production, and logistics as well as managing comprehensive flow of information. CPS is a complex system that mandates flexible integration of various technologies. It is necessary to develop methodologies for interoperability and integration for a CPS development. This paper introduces a viable CPS architecture based on heterogeneous systems and technologies such as manufacturing execution system (MES), product lifecycle management (PLM), process mining (PM), discrete event simulation (DES), and virtual reality (VR) and its application case. The architecture and practice will help practical CPS development in actual manufacturing enterprises. Future research topics such as development of CPS based on cloud computing for SMEs and development of standards for interoperability within CPS are also discussed.